2004
DOI: 10.1080/13607860410001649626
|View full text |Cite
|
Sign up to set email alerts
|

Special Section—Behavioral symptoms of dementia: their measurement and intervention. Caregiver interventions for passive behaviors in dementia: links to the NDB model

Abstract: Passive behavior (PB) in persons with Alzheimer's disease (PWAD) has been overlooked despite recognition that it occurs on a daily basis and is often resistant to interventions. The purpose of this study was to describe how the experience of passivity was for the caregiver and the PWAD, factors that precipitated PB, caregiver responses that promoted engagement, and caregiver responses that intensified PB, as well as activities initiated by caregivers over the past month that reduced passivity in the person wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Some of the participants reported feeling powerless and left out of the decision‐making about their care, although not all of them fought against this. As discussed by Colling (2004), passive behaviour can also be a potential reaction to unanticipated events or stress and can be in itself a form of protest. Some participants were less accepting of the loss of control and battled against it with various means including voicing their anger or resisting interventions from the staff.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the participants reported feeling powerless and left out of the decision‐making about their care, although not all of them fought against this. As discussed by Colling (2004), passive behaviour can also be a potential reaction to unanticipated events or stress and can be in itself a form of protest. Some participants were less accepting of the loss of control and battled against it with various means including voicing their anger or resisting interventions from the staff.…”
Section: Resultsmentioning
confidence: 99%
“…This contrasted with another study (Song and Algase, ) that reported motor busyness and negative verbalization as negative predictors of eloping behavior (study participants in the latter study were, however, more cognitively impaired and from long‐term care facilities). Passivity in persons with dementia may “reflect needs associated with loss of control and feelings of helplessness” (Colling, ). Hence, the possibility that eloping behavior is a manifestation of this helplessness in them versus “active coping,” a theory congruent with the need‐driven dementia‐compromised behavior model (Algase et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this perspective, research has found that caregivers manage BPSD in part by adapting the social or physical environment in ways that minimize the PLWD's exposure to stressors (Moore, Ozanne, Ames, & Dow, 2013). Similarly, other studies show that caregivers with nonconfrontational approaches to BPSD that are sensitive to the PLWD's level of functioning (e.g., not challenging his or her understanding of events or situations) report more effective management of these symptoms and less decline in feelings of competence than those who use corrective or punitive tactics which could amplify stress within the care dyad (Colling, 2004;de Vugt et al, 2004;Harvath, 1994).…”
Section: Introductionmentioning
confidence: 91%
“…It is important to further enhance understanding of caregivers’ views about how they manage BPSD for at least three reasons. First, the few studies on this topic have limitations including a focus on behavior-specific management (e.g., wandering, passivity) (Colling et al, 2004; Dodds et al, 1994) and the consideration of general response orientations (e.g., being calm, patient, or positive) more than distinct strategies (e.g., using written prompts) (de Vugt et al, 2004; Harvath, 1994; Huis in het Veld et al, 2016; Turner et al, 2015). As a consequence, much remains unknown about particular approaches that caregivers use to manage a range of behaviors.…”
Section: Introductionmentioning
confidence: 99%